Views about vaccines and how views changed during the COVID-19 pandemic among a national sample of young gay, bisexual, and other men who have sex with men - Daniel Marshall; Annie-Laurie McRee; Amy L. Gower; Paul L. Reiter (Taylor & Francis Group, 2023)
ABSTRACTWe examined perceptions of vaccines and changes during the coronavirus disease 2019 (COVID-19) pandemic. From 2019 to 2021, a national sample of young gay, bisexual, and other men who have sex with men completed an open-ended survey item about vaccine perceptions. Analyses identified themes and polarity (negative, neutral, or positive) within responses and determined temporal changes across phases of the pandemic ("pre-pandemic," "pandemic," "initial vaccine availability," or "widespread vaccine availability"). Themes included health benefits of vaccines (53.9%), fear of shots (23.7%), COVID-19 (10.3%), vaccines being safe (5.6%), and vaccine hesitancy/misinformation (5.5%). Temporal changes existed for multiple themes (p < .05). Overall, 53.0% of responses were positive, 31.2% were negative, and 15.8% were neutral. Compared to the pre-pandemic phase, polarity was less positive for the widespread vaccine availability phase (odds ratio = 0.64, 95% confidence interval: 0.42-0.96). The findings provide insight into how vaccine perceptions change in concert with a public health emergency.